Cardiometabolic parameters and novel hematological indices in women with migraine: Novel hematological indices in migraine - Klisic, Aleksandra; Tmusic, Ana (Journal of Medical Biochemistry, 2026)
Objective: The pathophysiological aspect of migraine has not been fully elucidated. It is assumed that inflammation is at the root of this disease. The goal of the research is to examine cardiometabolic and novel hematological indices in patients with migraine. Methods: A total of 50 women diagnosed with migraine were included in the study. Women were recruited during pain-free periods between pain attacks. The control group consisted of 25 age-matched healthy women. The MIDAS score (Migraine Disability Assessment score) was calculated. Results: Women with migraine had higher levels of uric acid (P=0.045) and higher activity of transaminases, AST (P<0.001) and ALT (P=0.003). Significantly lower numbers of neutrophils and RDW-CV (%), and higher platelet count (PLT) and PCT were shown in subjects with migraine. The derived hematological parameters, i.e., NLR, dNLR, M-GLR, and PDW/PCT, were significantly lower in the group of women with migraine compared to the control group, while PNR was significantly higher in the migraine group. Among the examined hematological indicators, PNR showed an excellent diagnostic accuracy (AUC=0.727), while other parameters (RDW, PLT, neutrophils, PDW/PCT, NLR, dNLR, M-GLR) showed good diagnostic accuracy (0.600<AUC<0.700). The largest number of women suffering from migraine (52.9%) had a MIDAS score of 11-20. Creatinine showed good diagnostic accuracy in predicting high MIDAS score (AUC=0.678). Conclusion: Women suffering from migraine have less favorable cardiometabolic status in comparison to healthy women. Blood count parameters and calculated indexes have good diagnostic accuracy for migraine. These parameters are cost-effective and easily available.